Gerenciamento do vocabulário do usuário em sistemas baseados em tagging - Silva, José Valderlei da (2009)
The diversity of existent tagging-based systems, each one centered in a distinct kind of object or resource, force users to maintain their vocabulary dispersed among several systems that adopt that approach, harming the maintenance of a well organized vocabulary of terms and hindering the processes of information categorization and retrieval. For this reason, in this dissertation we defined an architecture for a system to the management of tags used in categorization systems. The main goal of the proposed architecture is to become a central and unique repository for the vocabulary of tags that users apply to categorize and to retrieve contents in tagging-based systems. The tag manager will aid the users in the organization and in the use of their personal vocabulary, reducing the difficulties and complexity in simultaneously working with several systems and vocabularies. The intention is to improve the quality of the categorizations and, consequently, of the information retrieval in taggingbased systems. In this dissertation, it is exposed the theoretical and practical discussions about the proposed system from tags management, its architecture and text examples that indicate its viability.